Synthesis and characterization of Ce0.6Sr0.4Fe0.8Co0.2O3-δ perovskite material： Potential cathode material for low temperature SOFCs - Sithole, Mlungisi N.; Omondi, Bernard; Ndungu, Patrick G. (Journal of rare earths, 2017)
A sol-gel method and a modified chemical vapour deposition technique were used to produce nanostructured Ce0.6Sr0.4Fe0.8Co0.2O3-δ materials at temperatures as low as 400 ℃. Powders were characterized using Fourier transform infrared spectroscopy （FTIR）, Raman spectroscopy, thermo gravimetric analysis, powder X-ray diffraction （XRD）, scanning electron microscopy （SEM） with energy dispersive X-ray spectroscopy, high resolution transmission electron microscopy （HRTEM）, and nitrogen sorption at 77 K. FTIR spectra showed that the sol-gel method resulted in residual carbon groups on the materials after calcination, while the Raman and XRD analysis confirmed that both synthesis methods resulted in cubic perovskite structure. However, the chemical va- pour deposition （CVD） method resulted in materials with a smaller crystallite size when compared to those prepared via the sol-gel route. The overall morphology of the powders was irregularly shaped aggregated particles as observed by SEM and HRTEM. In addition, HRTEM analysis showed that the materials were highly crystalline. Textural analysis revealed the powders had some mesoporosity, and the surface areas were 76.69 and 65.90 m2/g for materials synthesized using the CVD and sol-gel methods, respectively. The synthesized perovskite powders were used to fabricate button cells employing samarium doped ceria （SDC） as the electrolyte and NiO/SDC as the anode materials. As cathode materials, the maximum power density observed was 308.4 mW/cm2 at 500℃.